Acoustic and spectroscopic characterization of glycol ethers in vitamin B7 over the range of temperatures (288.15, 293.15, 298.15, 303.15) K - Swati Bhathley; Nabaparna Chakraborty; Kailash Chandra Juglan (Chemical Thermodynamics and Thermal Analysis)
Density (ρ) and ultrasonic speed (u) of butoxyethanol and phenoxyethanol in aqueous solution of biotin concentrations (0.0012, 0.0017, 0.0022) mol·kg−1 at varying temperature range (288.15, 293.15, 298.15 and 303.15) K at 0.1 MPa were measured using Anton Paar DSA 5000 M. The volumetric and acoustical properties such as apparent molar properties (V∅), partial molar volume (V∅0),partial molar volume of transfer (ΔV∅0),apparent molar isentropic compression (K∅),partial molar isentropic compression (K∅0),partial molar isentropic compression of transfer are computed using the experimental data of density (ρ) and ultrasonic speed (u). This investigation is useful to understand the solvation behavior of biotin. Additionally, partial molar expansibilities (E∅0) along with their first order derivatives (∂E∅0/∂T)pare determined using the obtained experimental data. These results are effective in understanding the nature of interaction occurring inside the solution. Further, pair and triplet coefficients are evaluated which determines the structure making and breaking ability of glycol ethers in aqueous solution of biotin. Also, spectroscopic study of solutions is mentioned in current research which reveals the nature and strength of bond formation and various interactions in the mixture. The present study suggests the molecular interaction between the solute and solvent present in aqueous solution of Biotin (Vitamin B7) as solvent, butoxyethanol (BE) and phenoxyethanol (PE) as solute.